Achtung für das Gesetz: Moral und Motivation bei Kant - Schadow, Steffi (Kant-Studien, 2013)
How can what we view as morally correct be the motive force for our actions? This work investigates this question with a view to Kant's action theory and moral philosophy, based on a close textual reading. The author argues that Kant's response to the question of moral motivation is a theory of practical rationality in which the practical importance of moral reasons as motives is made understandable through a theory of moral-rational sensibility. Steffi Schadow, Universität Bremen.